The roles of business firms in protecting natural environment: an Islamic perspective - Mhd. Sarif, Suhaimi; Ismail, Yusof (2014)
This paper argues that business firms have fiduciary duties, roles and responsibilities to provide protection to the natural environment as a mean to achiave business sustainability. However, the conventional business argues that the only obligation is to maximize profit within the legitimate means. The study uses an Islamic perspective in managing business, the natural environment and sustainability based on the framework of Islamic Jurisprudence of the environment (Fiqh al-Bi’ah fi al-Islam) by Mustafa Abu-Sway, particularly the relationship between human beings and the environment (vicegerency, subjection, and inhabitation). The study used note taking approach in the personal interview with 20 respondents, which comprised five (5) policy makers, 10 business leaders, and 5 community leaders in Malaysia and Thailand. The results of the study showed insignificant difference despite different geographical and political administration between Thailand and Malaysia. Policy makers from both countries were convinced that business sectors should include the natural environmental protection agenda into the business policies as part of the corporate social responsibility. The community leaders from both countries concurred with the policy makers that the business sectors should be more proactive in protecting the natural environment despite the ultimate business responsibility. Nevertheless, business sectors disagreed to burden the business solely with the responsibility to protect the natural environment as the duty to protect the natural environment is collective duties and responsibilities. The feedback from the informants suggest that policy makers, community leaders and business owners should revisit two duties and responsibilities from Islamic perspective to protect the natural environment and business sustainability, namely “subjection” and “inhabitation.” However, the results are not generalizable due to inadequate insights about the duties and responsibilities to protect the natural environment and to gain sustainability in business from Islamic perspective.